(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
The study examined the multi-faceted effects of armed robbery on business activities in the Lafia metropolis of Nasarawa State, Nigeria. The main objectives are to find out the causes of armed robbery, to identify the effect of armed robbery on business activities, the economic impact of armed robbery on the individual employee, the business owners, the social consequences on community dynamics, and to explore the measures put in place to control the menace of armed robbery in the society, through a comprehensive sociological analysis. Social control theory and strain theory of crime were adopted for the study. The study adopted a descriptive method. Based on the findings of the study, unemployment, lack of education, government policies on businesses, and peer influence are the major causes of armed robbery in the Lafia metropolis. The study revealed that armed robbery activities have a significant effect on business activities, the social life of the people, and psychological trauma for both the employers and employees in the Lafia metropolis. The study recommends that parents should be encouraged to monitor their children to avoid bad influences, which will reduce crime; strict and quick response to crime scenes by law enforcement agencies will reduce armed robbery; adequate punishment for offenders regardless of their social or economic status will reduce armed robbery, creation of job opportunity and youth empowerment programmed will reduce armed robbery in Lafia LGA.